Identification of Tissue-Specific Expressed Hub Genes and Potential Drugs in Rheumatoid Arthritis Using Bioinformatics Analysis - Xing, Xuewu; Xia, Qun; Gong, Baoqi; Shen, Zhongyang; Zhang, Yingze (Frontiers in Genetics, 2022)
Background: Rheumatoid arthritis (RA) is a common autoimmune disease characterized by progressive, destructive polyarthritis. However, the cause and underlying molecular events of RA are not clear. Here, we applied integrated bioinformatics to identify tissue‐specific expressed hub genes involved in RA and reveal potential targeted drugs. Methods: Three expression profiles of human microarray datasets involving fibroblast-like synoviocytes were downloaded from GEO database, the differentially expressed mRNAs, miRNAs and lncRNAs between normal and RA synovial samples were screened using GEO2R tool. BioGPS was used to identified tissue-specific expressed genes. Functional and pathway enrichment analyses were performed for common DEGs using the DAVID database, and the protein-protein interaction network of common DEGs was constructed to recognize hub genes by the STRING database and visualized with Cytoscape software. Based on receiver operating characteristic curve, we further investigated the prognostic values of tissue‐specific expressed hub genes in RA patients. CMap was run to identify novel anti-RA potential drugs. The DEM–DEG pairs and ceRNA network containing key DEMs were established by Cytoscape. Results: We obtain a total of 418 DEGs, 23 DEMs and 49 DELs. 64 DEGs were verified as tissue-specific expressed genes, most derive from the hematologic/immune system (31.25%). GO term and KEGG pathway enrichment analysis showed that DEGs focused primarily on immune-related biological process and NF-κB pathway. 10 hub genes were generated via using MCODE plugin in Cytoscape. Among them, SPAG5, CUX2 and THEMIS2 were identified as tissue‐specific expressed hub genes, these 3 tissue‐specific expressed hub genes have superior diagnostic value in the RA samples compared with OA samples. 5 compounds rank among the top five in connectivity score. In addition, 5 miRNAs were identified to be key DEMs, the lncRNA–miRNA–mRNA network with five key DEMs was formed. The networks containing tissue‐specific expressed hub genes are as follows: ARAP1-AS2/miR-20b-3p/TRIM3, ARAP1-AS2/miR-30c-3p/FRZB. Conclusions: This study indicates that screening for identify tissue‐specific expressed hub genes and ceRNA network in RA using integrated bioinformatics analyses could help us understand the mechanism of development of RA. Besides, SPAG5 and THEMIS2 might be candidate biomarkers for diagnosis of RA. LY-294002, trichostatin A and troleandomycin may be potential drugs for RA.